President Joko Widodo’s foreign policy shift on Egypt? Analysis of President Abdel Fattah Al-Sisi’s visit to Indonesia in 2015 - Tunggal, Aprilia Restuning; Burdah, Ibnu; Masrukhin, Mohammad Yunus; Setawati, Siti Mutiah; Ikhwan, Munirul; Uzair, Achmad (Edelweiss Applied Science and Technology, 2024)
This dissertation research aims to analyze and answer Indonesia’s foreign policy towards Egypt which has been running since the time of President Soekarno to President Joko Widodo. During the time of President Soekarno, Indonesia’s foreign policy towards Egypt was in a very strong or ideal position. This turns out to be different from the time of President Soeharto, who was in quite a worrying position. Efforts to strengthen Indonesia’s foreign policy towards Egypt were carried out through President Soeharto’s state visit to Egypt as carried out by President Soekarno. State visits to Egypt became a continuing tradition for Indonesian foreign policy during the period of Presidents Abdurrahman Wahid, Megawati and Susilo Bambang Yudhoyono. The transition of Indonesian leadership from SBY to Jokowi apparently had an influence on Indonesia’s foreign policy tradition towards Egypt, which was originally structured to change. President Jokowi’s absence from visiting Egypt on several occasions has increasingly become a big question mark and has become an unprecedented problem in Indonesia’s foreign policy. This research answers why President Joko Widodo’s foreign policy in relation to Egypt looks different from his predecessor, as well as what considerations are the background to President Jokowi’s policy of not visiting Egypt. The type of research is qualitative research. The research method uses case studies with the primary data obtained through interviews and secondary data obtained through documentation data collection techniques and literature study. The theoretical approach used is foreign policy, psychological concepts in foreign policy making. This research finds that Indonesia’s foreign policy towards Egypt during President Jokowi’s leadership has undergone changes from the traditions of previous presidents. This change was marked by the absence of President Jokowi’s visit to Egypt and Indonesia’s current foreign policy priorities which prioritize economic cooperation and investment with China, the UAE and Saudi Arabia. Meanwhile, the factors that influenced President Jokowi’s considerations in his policy of not visiting Egypt were due to the domestic situation in Egypt after the Arab Spring which had not fully improved, President Jokowi’s individual background and President Jokowi’s cognitive (psychological) considerations regarding the information he believed.